Elements of tourist attractions in the Bardi region (Albayan Scientific Journal, 2023)
The study dealt with the elements of tourism development in the city of bardiThis is due to the importance of tourism as an important economic sector that can bring hard currency and provide new job opportunities. This presentation also contributes to how to exploit these components in the development of the tourism industry, based on its characteristics and characteristics.Keywords: Ingredients, bardi, Tourism Geography.
Keywords: Ingredients; bardi; Tourism Geography